A name without a body: Ovid’s Tristia 3.4a - Fonseca Junior, Adir de Oliveira (Classica - Revista Brasileira de Estudos Clássicos, 2022)
This article aims to provide a close analysis of Tristia 3.4a, focusing on Ovid’s paradoxical relationship with power (potestas) in the poem. While advising his addressee to shun ambition and keep far from all magna nomina, Ovid himself seems to insist on the idea that, despite his exile in the region of Pontus, his own name (i.e. his reputation) is powerful and survives in Rome. Thus, I will argue that Tristia 3.4a ultimately suggests a dualism between Ovid’s name and his actual (and real) self.